Political Communication and Digital Diplomacy Through Narrative Strategy in The Issue of Tariff Wars: Framing Analysis of Social Media Posts the Governments of America, China and Germany - Inadia Aristyavani; Edi Nurwahyu Julianto; Suci Rahmah YF; Mira Natalia Pellu; Prasetya Yoga Santoso (CV Putra Publisher, 2026)
This study aims to analyze the narrative strategies used by the United States, China, and Germany in addressing the tariff war, focusing on the concepts of political communication, narrative strategy, and soft power. Political communication functions as a tool to shape public perception through the messages conveyed by political actors. Narrative strategy is used to frame the issue of the tariff war according to each country's political interests, while soft power relates to efforts to influence other countries through attraction and legitimacy rather than military power. The study employs a framing analysis method with purposive sampling, analyzing social media posts from four Twitter accounts representing the United States (President, VP), China (Ministry of Foreign Affairs), and Germany (Ministry of Foreign Affairs) during the period from April 3 to 10, 2025. The results show that the United States (U.S) frames the tariff war as a response to domestic economic issues, emphasizing economic independence and nationalism. Meanwhile, China frames the U.S. tariff policy as a violation of the multilateral trade system based on rules, focusing on resisting unilateralism. On the other hand, Germany emphasizes diplomacy and negotiation as a more rational and balanced solution. These differences in framing reflect the national interests and narrative strategies employed by each country to influence global public opinion through soft power. This study provides insights into how narrative strategies and framing can shape international public perception and influence global trade policies.